DEVELOPING STUDENTS' SPIRITUALITY: ANALYSIS OF THE VALUES OF BELIEF AND MORALITY IN THE BOOK OF AL-HIKAM - Muhamad Ansori Ansori; Zulfamanna Zulfamanna; Muh. Dzihab Aminudin S; Muhamad Azmi; Suhadi Suhadi (Nurul Jadid University, Paiton Probolinggo, East Java, 2026)
This study aimed to explore the values of aqidah (Islamic creed) and akhlaq (morality) in Ibn 'Athaillah Assakandari’s Al-Hikam and their role in the spiritual and moral development of contemporary adolescents. Using a qualitative descriptive-analytical approach, data were collected through in-depth interviews with ten purposively selected students actively engaged in Islamic spiritual activities. The findings indicated that key teachings from Al-Hikam including tawhid (divine unity), sincerity, self-reflection (muhasabah), patience, and ma‘rifatullah (gnosis of God) facilitate spiritual transformation by enhancing emotional resilience, moral stability, and a deeper sense of purpose. The study indicated that Sufi-based soul development, as presented in Al-Hikam, offered a relevant and effective pedagogical framework for addressing the psychological and moral challenges of youth in a globalized, digital era. The implications of this study highlight that integrating classical Sufi teachings into formal and non-formal education can enhance not only religious understanding but also emotional resilience, social responsibility, and ethical decision-making among adolescents.